Metodologi Penafsiran QS. al-Fatihah Dalam Kitab Tafsir Safwat al-Tafasir Karya ‘Ali al-Sabuni - Amrullah Harun; Harris Kulle; Teguh Arafah Julianto; Ahmad Taqiyuddin Takdir (AL-AQWAM: Jurnal Studi Al-Quran dan Tafsir, 2022)
This research discusses the interpretation of ‘Ali al-Sabuni in the interpretation of QS al-Fatihah in the interpretation book of Safwat al-Tafasir. The formulation of the problem in this research includes: how ‘Ali al-Sabuni is interpreted in interpreting QS al-Fatihah in the interpretation book of Safwat al-Tafasir. The data collection technique used in this research as a whole is library research because the source of the research is related written data. With the topic of the problems discussed using descriptive analysis The findings of this study are based on the interpretation of ‘Ali> al-Sabuni in the interpretation book of Safwat al-Tafasir, interpreting QS al-Fatihah using interpretation sources from “bi al-Ma’sur” and “bi al-Ra’yi”. Judging from several methods that have been introduced by the commentators, and by looking at the workings and also the characteristics of some of these methods, the research concludes that the interpretation book of S{afwat al-Tafasir uses the tahlili method. The interpretation of ‘Ali al-Sabuni who always examines each verse by paying attention to the specter of “balaghah”, resembles that of al-Adabi wa al-Ijtima’i.